PREVENTIVE ZINC SUPPLEMENTATION EFFECT ON REDOX STATUS IN RAT MODEL OF MAFLD - Eugenia R. Nikonorova; Alexandr A. Nikonorov; Elizaveta V. Popova; Eduard F. Agletdinov; Anton I. Sinitskii; Alexey A. Tinkov (Siberian Journal of Life Sciences and Agriculture, 2023)
Background. Oxidative stress plays an important role in the pathogenesis of metabolic-associated fatty liver disease (MAFLD). Antioxidant trace elements as cofactors of antioxidant enzymes and metalloproteins are involved in this process. Zinc being an important antioxidant may have a positive effect on the treatment of liver pathology. The study aimed to assess the effect of preventive zinc supplementation on MAFLD in rats.